The Impact Of Liquidity And Profitability On Stock Prices In The Gas And Oil Sector 2020–2024 - Reni Amsa; Agung Widhi Kurniawan; Nurman (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
The oil and gas sector is a strategic sector that plays an important role in supporting the Indonesian economy, but during the 2020–2024 period, this sector experienced stock price fluctuations that were not in line with the company's financial performance. This problem prompted this study, which aims to analyze the effect of liquidity and profitability on stock prices in oil and gas sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This study uses a quantitative approach with multiple linear regression methods and secondary data in the form of annual financial reports from 12 oil and gas sub-sector companies obtained through the official IDX website using a purposive sampling technique. The results of the study indicate that the liquidity variable as measured by the Current Ratio (CR) and profitability as measured by the Net Profit Margin (NPM) do not have a significant effect either partially or simultaneously on stock prices. The coefficient of determination (R²) value of 1.8% indicates that stock price variations are more influenced by external factors such as fluctuations in world oil prices, macroeconomic conditions, and energy market sentiment. This study concludes that internal financial ratios have not become the main determinant in stock price movements in the oil and gas sector, so investors need to consider global external factors in making investment decisions.